TRANSFORMATION OF URBAN LANDSCAPEIN LATGALE REGION ON CHANGE OF 20- 21 CENTURIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The paper deals with transformation of urban landscape in the 2 cities and 12 towns of Latgale region on change of 20-21 centuries, in the period from 1990 to 2007. Article provides information about factors and social economics processes that have influence on urban landscape structure and quality. The paper have a look at changes of land use structure, demographical processes, urban environmental quality, dynamics of urban transportation system and intensity of construction works in the cities and towns of Latgale region. The results establish disparities between scopes and directions of urban landscape transformation among different ranks of urban settlements.